Effects of silver nanoparticles doping on morphology and luminescence behaviour of ferroelectric liquid crystals Langmuir–Blodgett films. Issue 12 (25th September 2016) - Kaur, Ramneek; Bhullar, Gurpreet Kaur; Raina, K. K.
ABSTRACT: We report the deposition of Langmuir–Blodgett (LB) thin films of low-weight dispersed composite systems of ferroelectric liquid crystals (FLCs)–functionalised silver (Ag) nanoparticles. Because of their amphiphilic nature the molecules form stable Langmuir monolayers, which were transferred to silicon substrates. We noticed that absorption wave numbers are present for each bond constituting FLC–nanoparticles composite system, ensuring a complete transfer of molecules from water sub-phase. XRD showed intense peaks at 2 θ = 3.2° due to the layer structure of FLC molecules. We infer from the morphology of LB films that doping of nanoparticles do not provide any hindrance to SmC* layer structure of FLC molecules. The photoluminescence study indicates blue shift in emission spectra and peak intensity increases with Ag nanoparticles concentration. GRAPHICAL ABSTRACT: